Beyond TAM: The impact of trust, privacy control and reliability on an individual’s intention to use a coronavirus contact tracing App - Ologeanu-Taddei, Roxana; Guthrie, Cameron; Fosso-Wamba, Samuel (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
Few empirical studies have explored the factors that influence the intention to use Coronavirus contact-tracing apps. Building on previous literature on technology acceptance, trust, privacy control and reliability, we propose an integrated model. The hypotheses are tested on a representative sample of 1000 citizens in France who installed a contact-tracing app. Trust was found to play a central role: it directly and strongly influenced use intentions and mediated the relationship between perceived ease of use and behavioral intentions. Reliability was found to be a major antecedent of perceived ease of use, and privacy control influenced perceived usefulness.